Primary hepatic large B-cell lymphoma following direct-acting antiviral treatment for hepatitis C - Yosra Zaimi; Myriam Ayari; Walid Cherifi; Feryel Letaief Ksontini; Shema Ayadi; Emna Bel Hadj Mabrouk; Myriam Jrad (BMJ Open Gastroenterology)
Hepatitis C virus (HCV) infection is a major public health concern worldwide, raising important medical and economic issues. HCV-related end-stage liver disease is one of the most common indications for hepatic transplantation. Chronic hepatitis C is also assimilated to a systemic disease because of multiple extrahepatic manifestations, including lymphoproliferative disorders. The revolution of HCV treatment with the advent of direct-acting antivirals has significantly improved the management with high antiviral efficacy and good safety profile compared with old regimens, thus allowing good outcomes on hepatic and extrahepatic symptoms. However, with the widespread use of these new agents, controversial concerns about unexpected increasing cases of hepatocellular carcinoma were reported. We now report the case of a patient presenting with HCV-related cirrhosis, treated with direct-antiviral therapy and diagnosed with primary hepatic lymphoma shortly after the end of the treatment.